Pelatihan Parenting bagi Masyarakat dalam Mengembangkan Karakter Anak di Kabupaten Mempawah - Andriati, Novi; Martin, Martin; Atika, Amelia; Hidayati, Novi Wahyu; Hendrik, Hendrik; Hastiani, Hastiani (LP2M INSURI Ponorogo, 2022)
Abstract: Community service aims to describe parental guidance towards children while at home. This activity is in the form of counseling on how participants can develop parenting, especially in managing children's schedules in learning according to changing times, so that tasks as parents can play an active and effective role, participants can increase children's enthusiasm in learning, participants can set schedules for learning activities at home, children's habits in behaving towards their elders and helping them when doing work at home. This service activity was carried out at the Kontor Hall of Sungai Bundung Laut Village, Mempawah Regency, this activity was carried out smoothly and there was an increase in parents in carrying out parenting for children, it was evidenced by the increase in children's learning achievements, accustomed to independent living and the formation of children's learning programs. This training encourages participants to follow it and get the job done faster and more efficiently.